Deep level defects in electron irradiated GaN based Light emitting Diodes - B. JAYASHREE (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
Indium gallium nitride (InGaN)-based devices are potential candidates for integration into Air Force communication and sensor platforms. In this study, the electrical and optical properties of 8 MeV electron irradiated Light Emitting Diode (LED) Chips are characterized for deep level defects using Deep Level Transient Spectroscopy (DLTS), I-V and spectral response measurements. The objective of the present study is to assess the radiation tolerance of LEDs when they need to be operated in a radiation rich environment. When InGaN is exposed to a beam of electrons, it is found that five different electron traps are generated with activation energies ranging from 0.2 - 2.0 eV. Three of these traps correspond to radiation-induced traps previously reported in GaN, and they are found to deepen significantly in the energy band gap with an increase in electron fluence. The total trap concentration increases with increase in electron fluence while the carrier lifetime is found to decrease with increase in fluence. I-V measurements indicate that 8 MeV electron irradiation does not have any significant effect on the operating voltage. There is no significant change in dominant wavelength of the emission spectra of LED chips, suggesting GaN-based LEDs seem to be radiation tolerant up to electron fluence of the order of 6.8x 1014 electrons/cm2.